Integration and Development of the Dairy Regions in the Eurasian Economic Union: Trends, Problems and Prospects - Raskaliyev, Timur Hasanovich; Yesmagulova, Nurgul Dyusenovna; Digilina, Olga Borisovna (Economy of Regions, 2019)
The paper focuses on the most important economic processes taking place in the dairy regions of the Eurasian Economic Union. The article reveals the specific features ofthe dairy sector’s development in the chosen regions in the context of Eurasian integration. Moreover, it discusses the challenges faced by the regions and prospects ofthe regional development. Consequently, we formulated some recommendations for solving current problems. We based our study on the theoretical developments of various scientists and economists, and statistical and other information. We applied various methods of investigation, including analysis, comparisons and econometric modelling. We outlined some of the study’s limitations related to a rather short history of the union’s existence and insufficiency of the available statistical information. The procurement price for milk depends on a number of factors. Using the modelling tool, we have shown this dependence on the example ofthe Republic of Tatarstan, which is the largest region-producer of milk in the union. The study’s scientific novelty is in determining the main directions of the dairy sector’s transformation in the regions. Furthermore, our research proposes a model for assessing the influence of the certain factors on procurement prices in the industry. The study’s results can be applied for developing and implementing the state and regional economic policies.